Autonomy vs. control: Quality assurance and governmental policy in Flanders - De Wit, Kurt; Verhoeven, Jef C. (Education Policy Analysis Archives, 2004)
Higher education in Flanders has seen some major changes in the 1990s. One of the key elements of the new higher education regulations was the quality assessment system. This exemplified best the government's policy of granting all institutions of higher education autonomy, making them responsible for their policies, while still keeping the quality of higher education somewhat under governmental control. In this article, we focus on the tension between the government's aim of improving and controlling the quality of higher education and universities ' concern for their autonomy. We describe the Flemish government's view on issues of quality in higher education and confront these with an account on the basis of case studies of how the quality assurance system was actually implemented in universities. We conclude that the model of the "market state" or the "evaluative state" is only realised partially in Flanders. The government is still interventionist when it comes to key policy issues